2004
DOI: 10.3109/s10165-004-0280-y
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and efficacy of low-dose methotrexate in patients with rheumatoid arthritis

Abstract: This article evaluates the relationship between the pharmacokinetics of methotrexate (MTX), its efficacy in the treatment of rheumatoid arthritis (RA), and serum folic acid (FA) levels. The pharmacokinetics of MTX was studied in 29 patients with RA treated with low-dose MTX. The weekly dose of MTX was given orally at 2-4 mg every 12 h over a period of 24-36 h. Blood samples were taken 4 h after the first administration in any given week. A Bayesian method was used to estimate individual MTX pharmacokinetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Using previously published measures of MTX disposition in these samples (35), we found that cellular accumulation of MTX was associated with the depletion of CH 2 THF, CHϭTHF, and 5mTHF, as well as the accumulation of folic acid and DHF (data are available from the author upon request). Changes in intracellular folate concentrations were consistently found to be most strongly associated with the accumulation of MTXGlu 1-2 , rather than MTXGlu [3][4][5][6][7] .…”
Section: Mtx Therapy and Folates In Jiamentioning
confidence: 99%
See 1 more Smart Citation
“…Using previously published measures of MTX disposition in these samples (35), we found that cellular accumulation of MTX was associated with the depletion of CH 2 THF, CHϭTHF, and 5mTHF, as well as the accumulation of folic acid and DHF (data are available from the author upon request). Changes in intracellular folate concentrations were consistently found to be most strongly associated with the accumulation of MTXGlu 1-2 , rather than MTXGlu [3][4][5][6][7] .…”
Section: Mtx Therapy and Folates In Jiamentioning
confidence: 99%
“…The majority of efforts to identify clinical biomarkers for MTX therapy have focused on measures of drug disposition. Despite a high degree of interindividual variability in plasma pharmacokinetics, plasma MTX has not been found to be consistently associated with drug response in inflammatory arthritis (5)(6)(7), and is of limited utility as a tool for therapeutic drug monitoring in these patients. The realization that MTX is metabolized intracellularly through the addition of glutamate residues, similar to endogenous folates, forming pharmacologically active species, has resulted in efforts to correlate clinical response with MTX polyglu-tamate concentrations in red blood cells (RBCs) (8).…”
mentioning
confidence: 99%
“…It was reported that improvement of inflammatory markers in RA patients is correlated with the time for which the serum MTX concentration is over 0.02 μM [20]. In this study, we measured only the maximum serum MTX concentration since it was not feasible to carry out frequent blood samplings in outpatients.…”
Section: Discussionmentioning
confidence: 99%
“…22) Yamanaka et al 23) reported that extensive methotrexate use effectively suppressed RA disease activity and inhibits disability progression in a single institute-based large observational cohort (IORRA). Kudo-Tanaka et al 24) suggests that early therapeutic intervention with MTX could safely prevent the development of RA in patients with recent-onset undifferentiated arthritis. Hiraga et al 25) reported that serum MTX measurements could be useful in determining individual patient regimens because the degree of improvement in C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR) correlated with the length of time the MTX concentration-time curve (AUC) remained above 0.02 µM in one week.…”
mentioning
confidence: 99%